The Relationship Between TV Advertising Cost and Brand Awareness Focus on : Food Category Product - Merriska, Augustine; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2012)
The fact that there is an emerging trend in the TV advertising number in the commercials industries and also the increasing number of TV channel in Indonesia will create such highly competitive media in promoting and marketing their brands. In the other words, these both conditions will also affect into the pattern of their media strategy due to achieve the high brand awareness among the customers. However, it may cause some difficulties for the TV advertisers in defining their media strategy since this situation also could be the opportunities for the media company in deciding the policy for their advertising rates. Due to the enormous amount of expense in executing this TV advertising strategy, this research will provide the information of the relationship of the total advertising cost among the product categories with their brand awareness achievement. There are several variables in this study in measuring the behavior of these advertisers; they are food product categories, advertising cost, number of ads and Top Brand Awareness Index. The data was obtained by using Arianna software from A.C. Nielsen and for the Top Brand Awareness Index are from the Marketing Magazine in February 2010. In this research showed a weak correlation between the advertising cost with the brand awareness achievement in Food category product in Indonesia due to there are several brands that have strong brand awareness because they have been gained for years ago. Keywords: TV Advertising, Brand Awareness, Food Product Category, TV Advertising Cost